Introduction to optimum design - Arora, Jasbir S. (Amsterdam ; Boston : Elsevier/Academic Press, 2004)
Introduction to Optimum Design is intended for use in a first course on engineering design and optimization. Virtually any problem for which specific parameters need to be determined to satisfy constraints can be formulated as a design optimization problem. The concepts and methods described in the text are quite general and applicable to all such formulations. Inasmuch, the range of application of the optimum design methodology is almost limitless, constrained only by the imagination and ingenuity of the user. Throughout the text, simple design problems involving two to three design variables and three to four constraints are solved in detail to illustrate fundamental concepts and basic ideas. The necessary results from optimization theory are stated and their implications are studied through application to engineering design problems. Theory and concepts of optimum design are explained only through examples and simple engineering applications. Several of the numerical procedures and concepts described in the text are useful in many other engineering courses and applications. * Allows engineers involved in the design process to adapt optimum design concepts in their work using the material in the text. * Basic concepts of optimality conditions and numerical methods are described with simple examples, making the material high teachable and learnable. * Classroom-tested for many years to attain optimum pedagogical effectiveness.
Introduction to design -- Optimum design problem formulation -- Graphical optimization -- Optimum design concepts -- More on optimum design concepts -- Linear programming methods for optimum design -- More on linear programming methods for optimum design -- Numerical methods for unconstrained optimum design -- More on numerical methods for unconstrained optimum design -- Numerical methods for constrained optimum design -- More on numerical methods for constrained optimum design -- Introduction to optimum design with MATLAB -- Interactive design optimization -- Design optimization applications with implicit functions -- Discrete variable optimum design concepts and methods -- Genetic algorithms for optimum design -- Multiobjective optimum design concepts and methods -- Global optimization concepts and methods for optimum design.
Includes bibliographical references (p. 683-685) and index.
Keywords: Engineering design -- Mathematical models; Electronic books